Assessment of Carbon Metabolism of Cherry Tomato Fruits: How Does Affects Potassium Biofortification During Crop Cycle at Postharvest Storage? - Christian Constan-Aguilar; Luis Romero; Begona Blasco; Juan Manuel Ruiz; Teresa Soriano (European Scientific Journal, ESJ, 2016)
In the present work, we evaluate the implementation of a K biofortification programme that increases the dose of this macronutrient in the nutrient solution for growing tomatoes. The aim is assess whether this treatment improves the response of fruits to postharvest for 21 days at 4°C. Three K treatments were applied during the crop cycle of the plants: 5, 10, and 15 mM of KCl. The enzymes involved in carbon metabolism and sugar concentration were studied, both on the day of harvest and after 21 days of storage in cold room at 4°C. Similarly, enzymes related to the metabolism of organic acids as well as their concentration were studied. The application of this supplement, aside from increasing K concentration in the fruits, stimulated the sucrose (Suc) degradation by sucrose synthase (SuSy) activity while increasing fructose (Fruc) and glucose (Gluc) as well as raising malate accumulation induced by the activity of PEPC and MDH enzymes during storage of 21 days at 4°C. The KCl treatments could be related to changes in carbon metabolism and suggest a protective role against cold storage, improving the quality of tomato fruits.